PRAANGGAPAN DALAM FILM SUSAH SINYAL KARYA ERNEST PRAKARSA - Patin, Patin; Priyadi, Antonius Totok; Muzammil, Ahmad Rabiul (Universitas Tanjungpura, 2024)
The research conducted on the film Susah Sinyal by Ernest Prakarsa was research with the aim of describing the types of presuppositions contained in the dialogue of the film Susah Sinyal by Ernest Prakarsa. This research uses a descriptive method in the form of qualitative research. The data source used in this research is the film Susah Sinyal by Ernest Prakarsa which was released in 2017. The data for this research is all the dialogue spoken by the characters in the form of words, phrases and sentences that give rise to the presuppositions contained in the film Susah Sinyal by Ernest Prakarsa. This research uses documentary study data collection techniques. The results of this research found 214 speech data that gave rise to presuppositions, consisting of 78 existential presupposition speech data, 14 factive presupposition speech data, 33 lexical presupposition speech data, 27 nonfactive presupposition speech data, 49 structural presupposition speech data, and 13 counterfactual presupposition speech data. It can be concluded that the most existential presuppositions and the least counterfactual presuppositions are found in the film Susah Sinyal by Ernest Prakarsa.